Exploration Of Subjective Norms Of Tourists In The Application Of Planned Behavior Theory To Predict The Intention To Visit Tourist Objects In Indonesia - Listiawati; Sulivyo, Lod; Dewi, Faye Maya; Arsadi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This research aims to explore a deeper understanding of the factors that influence tourists' intentions to visit tourist attractions in Indonesia using the Planned Behavior Theory (TPB) approach. This research focuses on exploring tourists' subjective norms, which is one of the main components in the TPB, along with attitudes and behavioural control. The research method involves an online survey targeting a sample of tourists who have visited or intend to visit tourist attractions in Indonesia. The research instrument consists of structured questions designed to measure critical variables in the TPB, with particular emphasis on subjective norms. Data analysis used descriptive and inferential statistical techniques to identify relationships between key variables. The research findings are expected to significantly contribute to understanding the factors that influence tourists' visiting intentions, as well as their implications for developing marketing strategies and managing tourist attractions in Indonesia. It is hoped that the results of this research can become a reference for tourism industry stakeholders, government and researchers in consumer behaviour and tourism to improve the management and development of tourist attractions in Indonesia to increase the attractiveness and competitiveness of tourist destinations globally.